2019
DOI: 10.1063/1.5108775
|View full text |Cite
|
Sign up to set email alerts
|

The validity of high pressure IR for detecting the interactions between β-cyclodextrin and imidazolium based ionic liquids

Abstract: The effects of alkyl side-chain length on the interactions between imidazolium ionic liquids (ILs) and β-cyclodextrin (β-CD) were studied at ambient pressure and up to 2.5GPa. No noticeable changes in the C-H band frequencies of 1-methyl-3-propylimidazolium hexafluorophosphate ([MPIM][PF6]) were observed upon β-CD addition under ambient pressure. Nevertheless, β-CD addition inhibited the formation of the [MPIM][PF6] aggregated structure under pressures of ≤0.7 GPa. As the pressure was raised to 1.1–2.5 GPa, [M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In comparison with pure [C 4 MIM][PF 6 ] at the pressure of 0.4 GPa (Figure 2b), the C 2 -H and C 4,5 -H absorption bands of [C 4 MIM][PF 6 ]/DNA mixture at 0.4 GPa (Figure 3b) show smaller frequency shifts under compression. Previous studies [26][27][28] revealed that high pressure can enhance the cluster structure interaction and lead to a band frequency shift. The hydrogen-bond network of an IL cluster structure may be disrupted, as some added molecules (such as DNA) may disturb the associations of ILs or cut large aggregations to small pieces.…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…In comparison with pure [C 4 MIM][PF 6 ] at the pressure of 0.4 GPa (Figure 2b), the C 2 -H and C 4,5 -H absorption bands of [C 4 MIM][PF 6 ]/DNA mixture at 0.4 GPa (Figure 3b) show smaller frequency shifts under compression. Previous studies [26][27][28] revealed that high pressure can enhance the cluster structure interaction and lead to a band frequency shift. The hydrogen-bond network of an IL cluster structure may be disrupted, as some added molecules (such as DNA) may disturb the associations of ILs or cut large aggregations to small pieces.…”
Section: Introductionmentioning
confidence: 98%
“…(Figure 4A,B) show drastic blue shifts in the pressure range from ambient to 0.7 GPa and mild blue shifts in the pressure range from 0.7 to 2.5 GPa. Previous studies indicated [26][27][28] that high pressure can easily shorten the imidazolium C-H bonds by the enhancement of weak C-H hydrogen bonding, which leads to a blue shift. Blue shifts of the pure [C 4 MIM][PF 6 ] C-H stretching band in Figure 4A (Figure 4A,B) Figure 4C show blue shifts at the pressure increase from ambient to 0.7 GPa and slight frequency shifts in the pressure range from 0.7 to 2.5 GPa.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations